CHARACTERISTICS OF STUDENTS AT SMP NEGERI 1 LHOKNGA ACEH BESAR - Indrawati; Siti Mayang Sari; Akmaluddin; Fitriani Manurung (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This article made with objective give knowledge to readers aboutcharacteristics participant educate so you can maximizing learning, that is withunderstand each characteristic participant educate from intelligence and stylediverse learning. So that learning can walk with fluent that is with evenlyunderstanding diverse students characteristics. With so, understandingcharacteristics participant educate that alone is whole pattern do or capabilitiesparticipant educate as results from heredity and environment, so determineactivity in reach ambition or goal. Because of that characteristics participanteducate is one very important component in planning learning. Writing articlethis use method observation and study library, with see various source orreference like books and some reference other related about the same materialwith the article I made. With thus, goals learning can achieved without mustgive pressure to participant educate. On the side it, with exists teacher'sunderstanding of characteristics in self participant educate can grow feelingcomfortable for study at school.